THE EFFECT OF RESISTANCE BAND EXERCISES ON INCREASING ARM POWER IN EXTRACURRICULAR VOLLEYBALL PLAYERS IN SMA NEGERI 5 MALANG ACADEMIC YEAR 2024/2025 - Yolla, Yolla Sekar Asti; Yuniarto, Andryas; Yunus, Mahmud (Journal of Strength and Conditioning, 2024)
This research aims to prove that a training program using Resistance Bands has an effect on increasing arm power in volleyball extracurricular players at SMAN 5 Malang. The research used a quantitative method with a pre-experimental approach type one group pretest-posttest, where one group of subjects who had been determined underwent initial measurements (pretest) before receiving treatment in the form of Resistance Band exercises. This training program lasts for 16 meetings with a variety of exercises specifically designed to increase arm power. After treatment, subjects underwent final measurements (posttest) using the Medicine Ball Test to assess changes in arm power. The research results show that there is a positive influence of the Resistance Band training program on increasing arm power in extracurricular volleyball players at SMAN 5 Malang for the 2024/2025 academic year.